PENINGKATAN KEMAMPUAN PRONUNCIATION VOCABULARY UNTUK PEMBELAJARAN BAHASA INGGRIS DENGAN TEKNOLOGI TEXT-TO-SPEECH DAN SPEECH RECOGNITION DI SEKOLAH DASAR YBPK MALANG - Yudhistiro, Kukuh; Silalahi, Elfrida Br. (Universitas Merdeka Pasuruan, 2021)
Learning methods in English subjects require the right strategy. Starting from the provision of laboratories and learning facilities to software. Generally, the learning material cannot be separated from material in the form of audio or video. However, some schools, especially schools that are in the limited category in terms of providing materials, need to do other ways so that their students can learn English well in class or independently. Text-to-speech and speech recognition technology implemented through software accompanied by images makes learning pronunciation and vocabulary more interesting and interactive for students who take extracurricular activities or study in English classes. This service helps extracurricular English teachers at SD YBPK Ngaglik Malang in completing and adding teaching methods not only through paper media, but also media that support interactive activities for students, both independently and in groups, resulting in an increase in pronunciation skills and vocabulary mastery.